2013
DOI: 10.1002/chir.22163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromatographic Conditions on Enantioseparation of Bovine Serum Albumin Chiral Stationary Phase in HPLC and Thermodynamic Studies

Abstract: Twelve chiral compounds were enantiomerically resolved on bovine serum albumin chiral stationary phase (BSA-CSP) by high-performance liquid chromatography (HPLC) in reversed-phase modes. Chromatographic conditions such as mobile phase pH, the percentage of organic modifier, and concentration of analyte were optimized for separation of enantiomers. For N-(2, 4-dinitrophenyl)-serine (DNP-ser), the retention factors (k) greatly increase from 0.81 to 6.23 as the pH decreasing from 7.21 to 5.14, and the resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The pH of running buffer solution can affect the ionization state of analytes and coating material as well as the EOF, thus impacting the separation efficiency. Because the isoelectric point of BSA (p I 4.7) and the limitations of BSA support were at pH 8.0 [25], the effect of buffer pH on chiral separation was investigated in the range of 5.0–8.0. Under this condition, BSA support on the capillary inner wall was negatively charged and all the target drugs (p K a values ranging from 4.4 to 13.1) were in the positively charged form.…”
Section: Resultsmentioning
confidence: 99%
“…The pH of running buffer solution can affect the ionization state of analytes and coating material as well as the EOF, thus impacting the separation efficiency. Because the isoelectric point of BSA (p I 4.7) and the limitations of BSA support were at pH 8.0 [25], the effect of buffer pH on chiral separation was investigated in the range of 5.0–8.0. Under this condition, BSA support on the capillary inner wall was negatively charged and all the target drugs (p K a values ranging from 4.4 to 13.1) were in the positively charged form.…”
Section: Resultsmentioning
confidence: 99%
“…Fu et al reported immobilization of BSA on magnetic Fe 3 O 4 nanoparticles through electrostatic adsorption interactions; though the chiral material was successful for separation of chiral drug enantiomers, the new material was susceptible to recycle use because of the unstable electrostatic interactions between BSA and the NPs. Using commercially available BSA HPLC columns (150 mm × 4.6 mm i.d., 5 μm particle size) from Guangzhou Research and Creativity Biotechnology, China, Wang et al enantiomerically resolved 12 chiral compounds on a BSA chiral stationary phase (CSP) in reversed-phase mode; chiral recognition mechanisms were discussed through thermodynamic studies, and the sample concentration was found to play a crucial role in separation of chiral samples, with the total amount of a sample usually being limited to the range of 0.25–1 μg. Furthermore, reversal of the enantiomer elution order was observed in BSA CSP studies through changing the mobile phase pH, the content of acetonitrile, or alcohol modifiers .…”
Section: Introductionmentioning
confidence: 99%